Medical management of heavy menstrual bleeding: understanding women's experiences - Prileszky, Gail (2013)
Introduction: Heavy menstrual bleeding is known to impact on health, wellbeing and social functioning. There is limited research examining women’s experiences of treatment for this complex condition. This longitudinal qualitative study explored women’s experiences of medical treatment for heavy menstrual bleeding with particular reference to women’s treatment preferences, quality of life and cultural variation.